Usahawan siswa UiTM 2023: Saranana Production - UiTM, MASMED (Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2023)
Saranana Production diusahakan oleh Sara Nurshazana dari UiTM Kedah.